Los textos de Virgilio y Ovidio en el "Orfeo en lengua castellana" (1624) de Juan Pérez de Montalbán - Arcaz Pozo, Juan Luis (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
This paper studies the use made by the author of the Orfeo en lengua castellana(1624) of the two main Latin sources which transmit the myth of Orpheus and Eurydice (Virgil, Georg. IV 457-527 and Ovid, Met. X and XI 1-84), in order to estimate in each case the importance these texts have in the redaction of the long poem by Pérez de Montalbán.